Solid‐state transformation of nanocrystalline phyllomanganate into tectomanganate: influence of initial layer and interlayer structure. Issue 5 (17th September 2014) - Grangeon, Sylvain; Lanson, Bruno; Lanson, Martine
<x xml:space="preserve">Abstract</x> In surficial environments, the fate of many elements is influenced by their interactions with the phyllomanganate vernadite, a nano‐sized and turbostratic variety of birnessite. To advance our understanding of the surface reactivity of vernadite as a function of pH, synthetic vernadite (δ‐MnO2) was equilibrated at pH ranging from 3 to 10 and characterized structurally using chemical methods, thermogravimetry and modelling of powder X‐ray diffraction (XRD) patterns. With decreasing pH, the number of vacant layer sites increases in the octahedral layers of δ‐MnO2 (from 0.14 per layer octahedron at pH 10 to 0.17 at pH 3), whereas the number of layer Mn3+ is, within errors, equal to 0.12 per layer octahedron over the whole pH range. Vacant layer sites are capped by interlayer Mn3+ sorbed as triple corner‐sharing surface complexes (TC sites). The increasing number of interlayer Mn3+ with decreasing pH (from 0.075 per layer octahedron at pH 10 to 0.175 at pH 3) results in the decrease of the average Mn oxidation degree (from 3.80 ± 0.01 at pH 10 to 3.70 ± 0.01 at pH 3) and in the lowering of the Na/Mn ratio (from 27.66 ± 0.20 at pH 10 to 6.99 ± 0.16 at pH 3). In addition, in‐plane unit‐cell parameters are negatively correlated to the number of interlayer Mn at TC sites and decrease with decreasing pH (from b = 2.842 Å at pH 10 to b = 2.834 Å at pH 3), layer symmetry being systematically hexagonal with a = b× 31/2. Finally, modelling of X‐ray diffraction (XRD) patterns indicates that crystallite size in the ab plane and along the c* axis decreases with decreasing pH, ranging respectively from 7 nm to 6 nm, and from 1.2 nm to 1.0 nm (pH 10 and 3, respectively). Following their characterization, dry samples were sealed in polystyrene vials, kept in the dark, and re‐analysed 4 and 8 years later. With ageing time and despite the dry state, layer Mn3+ extensively migrates to the interlayer most likely to minimize steric strains resulting from the Jahn–Teller distortion of Mn3+ octahedra. When the number of interlayer Mn3+ at TC sites resulting from this migration reaches the maximum value of ∼ 1/3 per layer octahedron, interlayer species from adjacent layers share their coordination sphere, resulting in cryptomelane‐like tunnel structure fragments (with a 2 × 2 tunnel size) with a significantly improved layer stacking order.